2018
DOI: 10.3389/fchem.2018.00127
|View full text |Cite
|
Sign up to set email alerts
|

Cerasomes and Bicelles: Hybrid Bilayered Nanostructures With Silica-Like Surface in Cancer Theranostics

Abstract: Over years, theranostic nanoplatforms have provided a new avenue for the diagnosis and treatment of various cancer types. To this end, a myriad of nanocarriers such as polymeric micelles, liposomes, and inorganic nanoparticles (NPs) with distinct physiochemical and biological properties are routinely investigated for preclinical and clinical studies. So far, liposomes have received great attention for various biomedical applications, however, it still suffers from insufficient morphological stability. On the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 117 publications
(159 reference statements)
0
13
0
Order By: Relevance
“…For example, Barbosa-Barros reported that bicelles have been used for drug penetration carrier through skin [64]. In addition, organic–inorganic hybrid bicelles named “cerasomes” were also developed [65]. These hybrid bicelles were reported to show a unique drug release profile under an acidic pH environment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Barbosa-Barros reported that bicelles have been used for drug penetration carrier through skin [64]. In addition, organic–inorganic hybrid bicelles named “cerasomes” were also developed [65]. These hybrid bicelles were reported to show a unique drug release profile under an acidic pH environment.…”
Section: Discussionmentioning
confidence: 99%
“…Anthracyclines are a class of anticancer medications which induce malignant cell apoptosis by affecting DNA function, inhibiting DNA synthesis, and thereby interfering with cell growth and proliferation. Among the drugs of this class, doxorubicin has been proved to be effective against a wide spectrum of malignancies including lymphoma and breast, thyroid, bladder, stomach, bone, and neural tissue cancers [8,9,10,11,12]. Paclitaxel is another broadly used anticancer medication.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of multiple drugs, and imaging agents, within HNCs on a large scale might be expensive as well as challenging. Further studies and optimizations will be required to eventually scale up the manufacturing process from the bench to clinical application [51]. The GMP manufactured theranostics nanomedicine should be simple, cheap, ultra-small, biodegradable, and easy to use.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%